HUBUNGAN PENGETAHUAN GIZI DAN KEBIASAAN SARAPAN DENGAN PRESTASI BELAJAR SISWA DI SMA NEGERI 3 KLUET UTARA TAHUN 2024 - ZUARI; T. Alamsyah; Khairunnas; Marniati (Jurnal Biogenerasi, 2025)
Academic achievement is one of the indicators of educational success influenced by various factors, including nutritional intake and breakfast habits. Eating breakfast plays an important role in improving concentration and memory, while nutritional knowledge fosters healthy eating habits that support the learning process. This study aims to analyze the relationship between nutritional knowledge and breakfast habits with academic achievement among students at SMA Negeri 3 Kluet Utara in 2024. A quantitative approach with a cross-sectional design was used. A total of 80 students from grades X and XI were selected using accidental sampling. The Chi-square test results indicated a significant relationship between nutritional knowledge (p = 0.002) and breakfast habits (p = 0.007) with academic achievement. Based on these findings, it is recommended that students enhance their nutritional knowledge and maintain regular breakfast habits to support better academic performance.